2017
DOI: 10.1111/1753-0407.12556
|View full text |Cite
|
Sign up to set email alerts
|

Recovered insulin production after thiamine administration in permanent neonatal diabetes mellitus with a novel solute carrier family 19 member 2 (SLC19A2) mutation

Abstract: Background: Solute carrier family 19 member 2 (SLC19A2) gene deficiency is one of the causes of permanent neonatal diabetes mellitus (PNDM) and can be effectively managed by thiamine supplementation. Herein we report on a male patient with a novel SLC19A2 mutation and summarize the clinical characteristics of patients with SLC19A2 deficiency. Methods: The genetic diagnosis of the patient with PNDM was made by sequencing and quantitative polymerase chain reaction. The clinical characteristics of PNDM were summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…SLC19 is a folate/thiamine transporter family, and there are three members (SLC19A1-3), of which SLC19A1 transports folates but not thiamine, and the other two transport thiamine but not folates (Zhao and Goldman, 2013). Mutations in the SLC19A2 gene, encoding thiamine transporter 1 (THTR1), were reported to be associated with thiamine-responsive megaloblastic anemia (TRMA) (Scharfe et al, 2000;Ozdemir et al, 2002;Ghaemi et al, 2013;Setoodeh et al, 2013;Sun et al, 2018;Amr et al, 2019), which is characterized by early-onset diabetes mellitus, anemia, and sensorineural deafness.…”
Section: Slc19a2mentioning
confidence: 99%
“…SLC19 is a folate/thiamine transporter family, and there are three members (SLC19A1-3), of which SLC19A1 transports folates but not thiamine, and the other two transport thiamine but not folates (Zhao and Goldman, 2013). Mutations in the SLC19A2 gene, encoding thiamine transporter 1 (THTR1), were reported to be associated with thiamine-responsive megaloblastic anemia (TRMA) (Scharfe et al, 2000;Ozdemir et al, 2002;Ghaemi et al, 2013;Setoodeh et al, 2013;Sun et al, 2018;Amr et al, 2019), which is characterized by early-onset diabetes mellitus, anemia, and sensorineural deafness.…”
Section: Slc19a2mentioning
confidence: 99%
“…Both the anemia and the diabetes may be responsive to thiamine treatment. A recent case study of a patient with a novel SLC19A2 mutation reported an increase in fasting C-peptide levels after 3 months of thiamine treatment and a subsequent decrease in insulin requirements [92]. By 23 months old, after 11 months of thiamine treatment, the patient’s C-peptide had increased by 0.24 ng/mL, and the patient no longer required insulin treatment.…”
Section: Rarer Causes Of Congenital Diabetesmentioning
confidence: 99%